Topical Administration of Nanostructured Lipid Carriers as a Viable Approach to Reduce Inflammation: A Review - Rajak, Prakash; Karmakar, Arka; Sarma, Santa; Bhuyan, Biman (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2025)
This review seeks to assess the potential of nanomaterials, specifically Nano-structured Lipid Carriers (NLCs), in mitigating challenges associated with inflammation-related disorders, with a particular emphasis on chronic ailments like arthritis. A comprehensive literature review spanning Web of Science, PubMed, and other scholarly repositories from 2000 to 2023 is conducted. Articles are selected based on their focus on NLCs and inflammation management, utilizing keywords, such as “nanomaterials,” “targeted drug delivery,” and “arthritis.” Exclusion criteria involve non-English studies or those lacking adequate detail on NLCs. Synthesized data provide an overview of the advantages, challenges, and prospects of NLCs in addressing chronic inflammatory disorders. This review also examines the therapeutic applications of nanotechnology, including targeted drug delivery and tissue engineering, particularly focusing on the intricate biological responses in chronic inflammation, often involving Non-steroidal Anti-inflammatory Drugs (NSAIDs). Moreover, the exploration extends to topical delivery methods to enhance control over medication concentration, with a review of lipid nanoparticles, such as liposomes and solid-lipid nanoparticles, highlighting their potential in augmenting drug permeation while addressing challenges like inadequate drug loading.NLCs have emerged as promising candidates for overcoming drug delivery challenges, particularly in arthritis treatment, with a focus on their advantages across diverse lipid compositions. The review underscores significant strides in inflammation management through NLC utilization, offering insights into future research directions.Moreover, it contributes to ongoing advancements in nanomedicine, emphasizing the pivotal role of NLCs in developing innovative therapeutic approaches for inflammation-related disorders, particularly arthritis. NLCs represent a promising avenue for effective interventions, signaling progress in nanotechnology-enabled therapeutics.
Keywords: nanostructured lipid carriers